DAMPAK KONFLIK INTERNASIONAL TERHADAP PERILAKU KONSUMEN KEPADA PERUSAHAAN ASAL AMERIKA YANG BEROPERASI DI INDONESIA - Wisnu Rayhan Adhitya; Tiara Reizsa Adhitya; Saniah Lidiya Hawani (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
This research aims to analyze and determine the impact related to the international conflict that occurred in the Middle East between the State of Israel and Palestine on the economic and business sectors in Indonesia. The many products and companies from the United States operating in Indonesia have become the target of anger among the Indonesian people due to rumors stating that the United States is the mastermind behind the conflict. The cause of this issue resulted in many calls for a boycott of products and companies originating from the United States, causing various problems in terms of company income and the fate of the employees who worked at the company. Of course, if these American products are boycotted by the Indonesian people, the company's sales will decrease, causing company losses which will also have an impact on reducing operational costs which will result in a reduction in workforce at each company so that it could become a new problem for Indonesia which causing the unemployment rate to increase due to this problem.